Toward pH independent oxygen reduction reaction by polydopamine derived 3D interconnected, iron carbide embedded graphitic carbon - Gangadharan, Pranav K.; Pandikassala, Ajmal; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2021)
Recent advancements on the development of nonprecious electrocatalysts with iron (Fe) incorporated active centers have generated confidence on realizing cost-effective proton exchange membrane fuel cells (PEMFCs). However, most of these catalysts that emerged as a substitution for the platinum supported on carbon (Pt/C) catalysts in oxygen reduction reaction (ORR) are active under basic conditions, and their feasibility in PEMFCs remains as a challenge. In this scenario, this work reports the synthesis of a Pt-free oxygen reduction electrocatalyst prepared by the annealing of polydopamine grown melamine foam. The prepared catalyst has a three-dimensional (3D) interconnected bilayer network structure possessing the carbon nitride backbone wrapped by graphitic carbon layer bearing iron carbides and nitrides as the active centers (3DFePDC). Interestingly, the 3D-FePDC catalyst displayed an ORR activity both under acidic and basic conditions. Whereas the ORR performance of 3D-FePDC closely matches that of the commercial Pt/C in the basic medium, it displays only a low overpotential value of 60 mV under acidic conditions compared to its Pt counterpart. The kinetics of ORR on 3DFePDC is found to be similar to the four-electron (4e) reduction pathway displayed by Pt/C. Testing of a PEMFC in a single cell mode by using 3D-FePDC as the cathode catalyst and Nafion membrane delivered a maximum power density of 278 mW cm(-2), which is a promising value expected from a system based on the nonprecious metal cathode. Ultimately, as a cost-effective catalyst that can effectively perform irrespective of the pH conditions, 3D-FePDC offers significant prospects in the areas like fuel cells and metal-air batteries which work in acidic and/or basic conditions.
Keywords: acidic medium; electrocatalyst; fuel cell; graphitic carbon; Iron carbide; nitrogen doping; nonprecious metal; oxygen reduction reaction